2007
DOI: 10.1016/j.ejca.2007.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-induced masking of ErbB2 and CD44-enhanced trastuzumab internalisation in trastuzumab resistant breast cancer

Abstract: Although trastuzumab, a recombinant humanized anti-ErbB2 antibody, is widely used in the treatment of breast cancer, neither its mechanism of action, nor the factors leading to resistance are fully understood. We have previously shown that antibody-dependent cellular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 47 publications
4
101
0
2
Order By: Relevance
“…Both stromal cells and tumor cells may provide HA to the TME, and our results demonstrate that an HA high TME contributes to limiting the access of NK cells and therapeutic antibody into the tumor. Although, while we have not observed reduced antibody binding to HA high tumor cells in vitro, receptor masking in HA high tumors in vivo may contribute to resistance to mAb therapy (34,35). Thus, enhanced tumor access of NK cells and antibody, as well as increased antibody binding to exposed target receptors, can be achieved by depletion of stromal HA with PEGPH20 treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Both stromal cells and tumor cells may provide HA to the TME, and our results demonstrate that an HA high TME contributes to limiting the access of NK cells and therapeutic antibody into the tumor. Although, while we have not observed reduced antibody binding to HA high tumor cells in vitro, receptor masking in HA high tumors in vivo may contribute to resistance to mAb therapy (34,35). Thus, enhanced tumor access of NK cells and antibody, as well as increased antibody binding to exposed target receptors, can be achieved by depletion of stromal HA with PEGPH20 treatment.…”
Section: Discussionmentioning
confidence: 95%
“…[19][20][21][22][23][24][25] Moreover, the overall response rate of women diagnosed with HER2-positive metastatic breast cancer and treated with trastuzumab as a single first-line agent is only 26%; that is, > 70% of HER2-overexpressing metastatic breast carcinomas show a resistance to trastuzumab ab initio. A variety of possible mechanisms of escape from trastuzumab appear to involve many of the same biomarkers that have been implicated in the biology of CS-like cells: e.g., the overexpression of the stem cell-related marker CD44, leading to a loss or blockage of the trastuzumab-binding site at the extracellular domain of HER2; 26,27 the upregulation of stem cell markers, such as CXCR4, β1 integrin or Notch-1, [28][29][30][31][32] leading to the activation of alternative pathways circumventing HER2 signaling and the upregulation of pro-survival mediators, such as the inhibitor of apoptosis survivin. 33 Accordingly, it has been suggested that, although trastuzumab effectively targets cancer-initiating cells, a clinical resistance to trastuzumab may counter-intuitively be driven by breast CSCs.…”
Section: Epithelial-to-mesenchymal Transition (Emt) Confers Primary Rmentioning
confidence: 99%
“…2). Despite its paradoxical HER2 gene amplification, ER/PR-negative JIMT-1 cells have repeatedly been classified as basal-like breast cancer cells mainly due to the fact that they express both basal CK5/ CK14 and luminal CK8/CK18 cytokeratins (11,13). Highresolution genomic profiles have confirmed that JIMT-1 cells have the closest resemblance to the HER2 + breast cancer subtype but also to the stem/progenitor (basal-like) breast tumors (23).…”
Section: Jimt-1 Breast Cancer Cells: a Model For Studying Her2-overexmentioning
confidence: 80%
“…Although significant amount of pre-clinical and clinical research has been dedicated to elucidate molecular mechanisms that could explain the appearance of acquired resistance to trastuzumab (7)(8)(9)(10), there have been few studies addressing the ultimate molecular mechanisms that could explain de novo (i.e. intrinsic or primary) resistance to trastuzumab (11)(12)(13). Indeed, HER2 status yet remains as the only available biomarker for selecting breast cancer patients for trastuzumab-based therapy.…”
Section: Introductionmentioning
confidence: 99%